A preliminary investigation of amino acid and acylcarnitine levels in neonates from the Tibet autonomous - Zhang, Chunyan; Dha, Drun; Cheng, Yuxuan; Ma, Ya; Meng, Yan; Tse, Drun; Ngawang, Dolma; Dekyi, Pedrun; Jiang, Tao; Shu, Yang; Cui, Jiayi; Li, Jing; et al. (Frontiers in Genetics, 2022)
Background: The purpose of the study was to investigate the levels of amino acids and acylcarnitines in newborns of the Tibet Autonomous Region for the first time and to provide an experimental basis for the diagnosis of genetic metabolic diseases. Methods: We detected concentrations of 43 kinds of amino acids, acylcarnitines and succinylacetone in the dried blood spots of 18482 newborns using liquid chromatography tandem mass spectrometry and diagnose the case by gene sequencing. We compared the indexes between Tibet and our lab, where most data come from an inland area and Han Chinese people. Then we compared amino acid and acylcarnitine levels of seven regions in Tibet and explored their impact factors. Results: We described the levels of amino acids and acylcarnitines in Tibet newborns using 95% confidence intervals. The distribution of amino acid and acylcarnitines were different in Tibet. Conclusion: This study has contributed to filling in the blanks of Tibet newborn screening, which should be considered in the newborn metabolic disease screening in this area.